The Impact of ESG Disclosure and Risk Management on Firm Value: Empirical Study in ASEAN - Yureza Rian Wibowo; Etty Gurendrawati; Gatot Nazir Muhammad (Journal of State Economic Research, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) disclosure and risk management on firm value in public companies within the Association of Southeast Asian Nations (ASEAN) during 2020–2024. The study employs a quantitative approach using balanced panel data from 272 public companies across ASEAN countries obtained from Refinitiv Eikon. Firm value is proxied by Price to Book Value (PBV), ESG disclosure is measured using ESG Score, while risk management is proxied by Earnings Before Interest, Taxes, Depreciation, and Amortization (EBITDA). Data were analyzed using panel data regression with the Fixed Effect Model (FEM). The results indicate that ESG disclosure has a positive and significant effect on firm value, while risk management has no significant effect. These findings suggest that investors increasingly consider sustainability, transparency, and corporate governance in investment decision-making. This study contributes to the literature on ESG disclosure, risk management, and firm value in emerging markets within the ASEAN region.